Evaluation of elastoplastic properties of brittle sandstone at microscale using micro‐indentation test and simulation. Issue 10 (5th June 2020) - Song, Rui; Wang, Yao; Sun, Shuyu; Cui, Mengmeng; Liu, Jianjun
Abstract: The micro‐indentation test has been regarded as an efficient tool to obtain the elasticity modulus and hardness of the minerals in rock, which is essential for studying the deformation‐crack mechanism of the pore structure. However, researches on microscopic plastic parameters have been rarely conducted. This paper develops a novel method to determine the microscopic initial strength and residual strength of brittle sandstone. A dimensionless analysis on the micro‐indentation curve of rock is conducted to acquire its key influencing factors of the elastoplastic properties, which include the initial cohesive force and the residual cohesive force. Then, small cylindrical rock samples are prepared for micro‐CT scanning and micro‐indentation test by a conical indenter to acquire the microstructure, indentation curve, and the microscale elasticity. The pore scale indentation simulation is conducted using the reconstructed rock models with different strength. The function between the indentation curve and strength is deduced by the parametric finite element method (FEM) study. Based on this function, the microscale initial strength and residual strength of the brittle sandstone are determined. The proposed method is validated by comparing the microscale numerical simulation results of uniaxial compression on the representative volume element (RVE) model of rock with the experimental results. A reasonable deviation is observed compared with the experimental benchmark data for the stress‐strain curves, as well as Young's modulus and uniaxial compression strength, proving the effectiveness of the proposed method. Abstract : This paper develops a novel method to determine the microscopic initial strength and residual strength of brittle sandstone. The proposed method is validated by comparing the microscale numerical simulation of uniaxial compression on the representative volume element (RVE) model of rock with the experimental results. The results show a reasonable deviation from the experimental stress‐strain curves, as well as the elasticity modulus and uniaxial compression strength, proving the effectiveness of the proposed method.